Influence of different anesthetic depth on postoperative delirium in elderly pre-frail patients undergoing abdominal surgery - Rongman Chen; Pengfei Hou; Wanxin Liu; Haiqi Mi; Shuaiying Jia; Jingyan Lin (Perioperative Medicine)
Abstract Purpose Monitoring anesthetic depth may reduce the incidence of postoperative delirium in patients undergoing general anesthesia. This study investigated the impact of varying readings of Cerebral State Index (CSI) on postoperative delirium in elderly pre-frail patients undergoing abdominal surgery. Methods A total of 150 elderly pre-frail patients aged over 65 years scheduled for selective abdominal surgery under general anesthesia were enrolled. Pre-frailty was defined as a 5-Item Modified Frailty Index (mFI-5) score of 1–2. Patients in the light anesthesia (LA) group were maintained at a CSI value between 50 and 59, while patients in the deep anesthesia (DA) group were maintained at a CSI value between 40 and 49. The incidence of delirium within 3 days postoperatively, as well as visual analog scale (VAS) scores, postoperative nausea, vomiting, and the 15-item quality of recovery (QoR-15) scale scores on the first postoperative day were recorded and compared. Results The incidence of postoperative delirium was approximately 14% lower in the light anesthesia group compared to the deep anesthesia group (P < 0.05). The QoR-15 scale scores on the first postoperative day were significantly higher in the light anesthesia group than in the deep anesthesia group (P < 0.05). In contrast, the VAS scores over the 2 days following surgery were significantly higher in the deep anesthesia group than in the light anesthesia group (P < 0.05). Conclusion The elderly pre-frail patients under light anesthesia (with high CSI score) may have lower incidence of postoperative delirium and better outcome. Trial registration ChiCTR2400083016, Date of registration: 15/04/2025.